OFR-83(2)-78 XVIth International Conference On Coal Mine Safety Research Washington, D.C., 1975 - Opening And Closing Sessions - Discussion Of Papers ? Introduction (The National Institute for Occupational Safety and Health (NIOSH), 1975)
The XVIth International Conference on Coal Mine Safety Research was divided into eight half-day technical sessions. In accord with the established practice of these conferences, at each session, presentation of the papers was followed by a discussion period. Questions and comments submitted in writing to the session chairman were answered or discussed by the authors of the relevant papers or by their representatives. These discussions were tape-recorded in the original language of the speaker and subsequently translated into English when necessary. Questions to which no answer was available at the time and a few comments that exceeded the scope of the session have been omitted.